Synthesis, spectral and photophysical properties of novel phthalocyanines bearing bulky phenantroxy moiety - Erdogmus, Ali; Ugur, Ahmet Lutfi; Memisoglu, Abdussamed; Erden, Ibrahim (ELSEVIER, 2013)
The synthesis, characterization, spectral and photophysical properties of soluble 9-Phenanthroxy substituted oxo-titanium (IV), zinc, magnesium and nickel phthalocyanines (1a, 1b, 1c and 1d) are reported for the first time. The new compounds have been characterized by elemental analysis, FT-IR, H-1-NMR spectroscopy, electronic spectroscopy and mass spectra. General trends are described for spectral, fluorescence properties and fluorescence quantum yields of these compounds in dimethylsulfoxide (DMSO) and toluene. All phthalocyanine complexes (1a to 1d) exhibited excellent solubility in organic solvents such as dichloromethane, chloroform, THF, toluene, DMF and DMSO. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Titanium; Zinc; Nickel; Fluorescence; Magnesium; AGGREGATION BEHAVIOR; OPTICAL-PROPERTIES; NANOPARTICLES; SUBSTITUENTS; DERIVATIVES; ALPHA; Optics